Justice: The root of american business ideology and ethics - McGowan, Richard (Journal of business ethics, 1990)
Although there are many conceptions of “Justice”, these different perceptions can provide many interesting insights into a business person's ethical standards as well as that person's decision-making processes. Using the Bishops' Pastoral Letter on the U.S. Economy as the basis for asking questions about “justice”, twenty-four business executives were interviewed about their conception of justice. An analysis of these interviews reveals that this group of businesspeople operated under very different conceptions of “Justice” at the Macroenvironmental and Microenvironmental levels. This result has some interesting implications not only for those scholars concerned with business ethics but for everyone who has a stake in business education.